The Impact of E-Commerce on Increasing the Revenue of Culinary UMKM in Prabumulih City: Dampak E-Commerce Terhadap Peningkatan Pendapatan UMKM Kuliner di Kota Prabumulih - Sukmawati, Emi (Media Ekonomi Prabumulih, 2024)
This study aims to determine whether E-Commerce has an impact on increasing the revenue of culinary UMKM in Prabumulih City. UMKM actors are required to keep up with the development of digital technology to remain competitive and not be left behind by technological changes. By doing so, they can meet the demands of the digital market and innovate further in digital technology to achieve better results. The presence of E-Commerce is expected to bring changes in increasing sales, which in turn will positively impact the revenue growth of UMKM actors in general and culinary UMKM actors in Prabumulih City in particular. The research results show that the calculated t-value is 2.407, which is greater than the t-table value of 1.985, with a significance level of 0.18, which is smaller than the error rate (alpha) of 0.05. This means that E-Commerce has a significant impact on increasing the revenue of culinary UMKM in Prabumulih City.